Proline and antioxidant enzymes protect Tabebuia aurea (Bignoniaceae) from transitory water deficiency - Freire, Fátima Conceição de Jesus; Pinheiro, Juliana da Silva; Santos, Jayne Silva; Silva, Arthur Gomes Lima da; Camargos, Liliane Santos de [UNESP]; Endres, Lauricio; Justino, Gilberto Costa (FapUNIFESP (SciELO), 2022)
Water deficiency is a major abiotic stress that limits biomass production and drives plant species distributions. We evaluate the effects of water deficiency on ecophysiological and biochemical parameters of seedlings of Tabebuia aurea. Plants were subjected to daily watering (control) and to stress by soil water deficiency for 29 days. Leaf area, plant biomass, gas exchange, SPAD index, maximum quantum yield (Fv / Fm), quantum yield of PSII (ΦPSII), superoxide dismutase (SOD) and L-ascorbate peroxidase (APX) activity, lipid peroxidation, and proline content were recorded. Plants responded to water deficit by reducing leaf area and accumulating proline. Stomatal conductance was reduced to limit the water loss by transpiration. However, limiting CO2 uptake caused reduction in photosynthesis and biomass. The excess of energy unutilized by photosynthesis reduced SPAD index and ΦPSII. As a result, we observed an increase in SOD and APX activity, protecting chloroplast membranes from further damages caused by lipid peroxidation. Our results indicate that T. aurea have capacity to survive under water deficiency reducing stomatal aperture, but affecting the rate of CO2 assimilation. Nevertheless, plants showed mechanisms to preventing damages to the photosynthetic apparatus. Such plasticity is an important adaptation for plants growing in dry environmental.
Keywords: antioxidant system; gas exchange; proline; tree species; water deficit